Pengelolaan Laboratorium Pendidikan Di Mas Jam’iyah Mahmudiyah Tanjung Pura - Endah Retno Suci; Pitriani Nasution; Sri Wahyuni Hasibuan; Fauzan Azmi (Fusion: Jurnal Pengabdian kepada Masyarakat, 2022)
The purpose of the counseling held by the community service implementing team is to provide understanding and knowledge to school principals, educators and education staff at MAS Jam'iyah Mahmudiyah about the management of the Education laboratory. This is done so that educators and education personnel who play a role in learning activities that will be carried out in educational laboratories can run well and support the development of the potential of students. Procurement of laboratories without management causes the use of laboratories as learning resources is not optimal. For this reason, counseling was held on how to manage educational laboratories in schools, especially at MAS Jam'iyah Mahmudiyah Tanjung Pura. The method of implementation of counseling is done by presentation and question and answer. The counseling material was delivered by presenting slide modules that had been prepared by the service team and distributed to participants. Participants listened to the explanations given by the community service team and asked questions related to the material. After providing an understanding of the Education laboratory and how to manage the Education laboratory, participants are expected to be able to apply it in learning activities, especially in the use of the Education laboratory at MAS Jam'iyah Mahmudiyah Tanjung Pura. From the results of observations, some of the obstacles faced in relation to the education laboratory are inadequate facilities at the educational institution.